TELAAH KRITIS HUKUM PERNIKAHAN BEDA AGAMA DALAM PANDANGAN ULAMA KLASIK DAN KONTEMPORER - Julaika Nasution; Irfa Waldi (Sharia Law and Justice Journal, 2025)
This study explores the legal and theological perspectives on interfaith marriage within Islamic jurisprudence, focusing on the views of classical and contemporary scholars. Interfaith marriage, particularly between a Muslim and a non-Muslim, has long been a subject of scholarly debate due to its complex implications for faith, family, and social harmony. While the Qur’an permits Muslim men to marry women from the People of the Book under certain conditions, the practice remains controversial among scholars. Some argue it is permissible with strict limitations, while others prohibit it entirely, especially for Muslim women. This paper examines various interpretations from different schools of thought (madhhab), analyzes Qur'anic verses and Hadiths related to the issue, and considers modern legal opinions from different Muslim-majority countries. The study concludes by highlighting the ongoing need for contextual ijtihad in addressing interfaith marriage within contemporary Muslim societies.